PENATAAN KAWASAN OBJEK WISATA ALAM DODOKU AER KONDE DESA WAWALI KECAMATAN RATAHAN - Walansendow, Agustinus; Kamumu, Nardiansyah; Kadamehang, Gerry; Pangkarego, Lidia S. (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2023)
Tourism has a very important influence and role in the development of a region. Southeast Minahasa Regency is an area that has a diversity of tourist attractions. The Dodoku Aer Konde natural tourist area is one of the superior tourist areas, with its attraction and beauty found in the clarity of the water and the cool and cool air. However, this tourist area still lacks attention, complete facilities are not available, some facilities are starting to break down, and the layout is not good. The research with the title